The Economics of Fashion Demand - Robinson, Dwight E. (Quarterly Journal of Economics, 1961)
I. Introduction: fashion and economics, 376. — II. The state of fashion theory, 380. — III. The economic foundations of fashion, 385; the pursuit of rarity, 385; factor of demonstrability, 387; fashion as demonstrated command over current factors of production, 390. — IV. Some implications for economic fields, 393; value and welfare, 393; economic competition and organization, 395; economic development and cycles, 396. — V. Conclusion, 398.